First endemic freshwater Gammarus from Crete and its evolutionary history—an integrative taxonomy approach - Hupało, Kamil (PeerJ, 2018)
The Mediterranean islands are known as natural laboratories of evolution with a high level of endemic biodiversity. However, most biodiversity assessments have focused mainly on terrestrial and marine fauna, leaving the freshwater animals aside. Crete is one of the largest islands in the Mediterranean Basin, with a long history of isolation from the continental mainland. Gammarid amphipods are often dominant in macrozoobenthic communities in European inland waters. They are widely used in biomonitoring and exotoxicological studies. Herein, we describe Gammarus plaitisi sp. nov., endemic to Cretan streams, based on morphological characters and a set of molecular species delimitation methods using mitochondrial cytochrome oxidase subunit I and 16S rRNA genes as well as nuclear 28S rDNA, ITS1 and EF1-alpha genes. The divergence of the new species is strongly connected with the geological history of the island supporting its continental origin.